Government Strategy in Addressing the Impact of Economic Growth and Energy Consumption on Environmental Degradation - Setiawati, Ririt Iriani Sri; Imamah, Fauziyah (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
The report discusses the serious environmental issues Indonesia's growing economy and rising energy use have brought about. In addition to examining government initiatives to lessen these impacts through sustainable development regulations, the goals include evaluating the connection between economic indicators and environmental results. The research employs a mixed-approaches strategy, combining quantitative and qualitative methods. The quantitative analysis, which employs time series data from 1991 to 2020, focuses on carbon dioxide emissions per capita as the dependent variable and GDP and energy consumption per capita as independent variables. Multiple linear regression using Ordinary Least Squares (OLS) evaluates these correlations. A thorough grasp of the relationship between economic growth, energy consumption, and environmental deterioration is provided by qualitative analysis, which entails a review of the literature to investigate government initiatives addressing environmental concerns. The study results show a substantial positive correlation between Indonesia's carbon dioxide (CO₂) emissions, energy consumption, and economic development. The analysis indicates that the ongoing economic activities driven by fossil fuel consumption will exacerbate environmental degradation without significant intervention, necessitating effective government policies for sustainable development and emission reduction. The study concludes that economic growth and energy consumption significantly contribute to Indonesia's environmental degradation, particularly through increased carbon dioxide (CO₂) emissions. It recommends that the government strengthen policies promoting sustainable energy use, increase investment in renewable energy technologies, and implement stricter regulations on industrial emissions. Additionally, fostering public awareness and education on environmental sustainability is crucial for effective long-term solutions.